ISLAMIC REBT COUNSELING TO IMPROVE THE VISUALLY IMPAIRED PEOPLE’S SELF ESTEEM - NURUL KAMILATUSSA’DIAH; NURODIN; AGUS TAMAMI (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2022)
Blind people are individuals who experience limitations in vision, and from these limitations some blind people have self-esteem problems. Re-increasing self-esteem can use rational emotive behavior therapy as a counseling approach to self-esteem. The target of this research is blind people. This research was conducted at the Bogor SLBN with 2 blind people, namely An. ADD and ZM. This research is a quantitative research with a single case experiment with an A-B-A research design or an Applied Behavior Therapy research design. This study uses intervention as a form of treatment to increase self-esteem. The self-esteem situation of the blind before the intervention was indicated as low self-esteem because they felt worthless, felt inferior, looked down on themselves, withdrew from the environment, had negative beliefs and imagination, this was evident from the pre-test answers that the counselee filled. The overall score of the ADD and ZM pre-test, which was initially 178 after being given an intervention, became 273. This can be seen from the overall post-test score that was carried out. The conclusion is that the application of Islamic-based rational emotive behavior therapy can increase the self-esteem of blind people. Thus, the application of Islamic-based rational emotive behavior therapy has the effect of increasing the visually impaired people's self esteem